Characteristics of Patients with End-Stage Renal Disease at Dialysis Unit Dr. Soetomo General Hospital Surabaya - Leny Silviana Farida; Muhammad Thaha; Dwi Susanti (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction: The prevalence of end stage renal disease (ESRD) in Indonesia is increasing over the last decade. Most cases highest risk factor are Diabetes Mellitus (DM) and hypertension. Other factors such as lifestyle and environment; both play important role in the development of ESRD. Thus, this study aimed to assess the characteristic of patient with ESRD.Methods: This was a descriptive study acquired by interviewing 126 patients with ESRD who have been undergoing continuous hemodialysis in dialysis unit of Dr. Soetomo General Hospital Surabaya for at least 3 months using questionnaire about history of disease, smoking habit, sex, and ethnic group. All data was analyzed using frequency distribution and percentage.Results: Form 126 patients, consist of 61 male patients (48.4%) and 65 female (51.6%). 45 patients (35.7%) have the history of DM; 98 patients (77.0%) of hypertension; 35 patients (27.8%) of hypertension and DM; and 19 patients (15.1%) have none of them. Later age adult (36-45 years old) has the largest group proportion (34.13%). There are 36 patients (28%) who are smokers. 108 patients (85.7%) are Javanese.Conclusion: Most of the patients have hypertension as the risk factor and in later age group adult. Characteristics of patient with ESRD is caused by multifactorial factors. Therefore, patient with high risk factor should be aware and do preventive steps in progressiveness of the disease.